Clinical and Radiological Parameters of HIV-Associated Pulmonary Tuberculosis in the Region with a High Prevalence of the Coinfection - Yu. V. Bazhenova; E. Yu. Zorkaltseva; S. N. Zhdanova; O. A. Vorobieva; N. Yu. Rozhkova (Туберкулез и болезни лёгких)
The objective of the study: to compare clinical, social, and radiological parameters of respiratory tuberculosis in patients with different HIV statuses in the region with a high prevalence of the coinfection.Subjects and Methods. The retrospective study of medical files of 80 patients with pulmonary tuberculosis was conducted; patients were divided into 2 groups, 40 patients each: TB/HIV Group – patients with pulmonary tuberculosis and HIV infection, TB Group – patients with pulmonary tuberculosis and negative HIV status. The groups were comparable by gender and age. The groups were compared with each other by certain parameters.Results. Considering clinical signs, patients from TB/HIV Group suffered from more pronounced intoxication syndrome (χ2 = 10.476; p < 0.0012) and respiratory disorders such as severe shortness of breath with difficult inspiration (χ2 = 4.505; p < 0.03). Versus TB Group, patients in TB/HIV Group were more likely to have drug (χ2 = 10.7; p < 0.001) and alcohol addiction (χ2 = 4.21; p < 0.039), suffered from more disseminated disease (χ2 = 8.47 p < 0.003) with small proportion of pulmonary tissue destruction (χ2 = 5.8; p < 0.05), had pronounced intrathoracic lymphadenopathy (χ2 = 9.8; p = 0.0017) and pleural effusion (χ2 = 3.8; p < 0.05). Slower radiological improvement of tuberculous changes during treatment was detected in patients with TB/HIV co-infection versus HIV-negative patients (χ2 = 3.8; p < 0.05).Compared to CD4 lymphocytes > 200 cell/μl, when CD4 level ≤ 200 cell/μl, the frequency of radiological signs typical of tuberculosis such as alveolar infiltration, destruction of lung tissue decreased in chest CT, while the frequency of atypical manifestations (interstitial changes such as frosted glass) increased.